PENGARUH BAHASA BANGSA EROPA DI TERNATE - Jainul Yusup (Universitas Khairun, 2019)
Ternate Malay Language (BMT) in the past become a second language for speakers of ethnic languages (local languages). While the first language is the language of each region. But when viewed developments today, more and more ethnic in North Maluku which uses Ternate Malay as a first language, including ethnic Ternate.Keywords: Language Influence, European Nations, Ternate, North Maluku.